2017
DOI: 10.1111/vop.12496
|View full text |Cite
|
Sign up to set email alerts
|

Punctate retinal hemorrhage and its relation to ocular and systemic disease in dogs: 83 cases

Abstract: The risk of PRH in dogs may be increased by certain ocular and systemic diseases. As the presence of PRH can be associated with underlying systemic disease in dogs, it may prompt further clinical investigation and diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Eye diseases in dogs may be caused by different pathogeneses, including neoplasia, trauma, infectious diseases, and genetics [6,7,8,9]. Furthermore, eye changes may occur secondary to systemic diseases such as diabetes mellitus [10] or hypothyroidism [11]. Congenital eye malformations might be caused by a genetic disposition, as well as by exposure to toxins [12] or infections of the mother during pregnancy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Eye diseases in dogs may be caused by different pathogeneses, including neoplasia, trauma, infectious diseases, and genetics [6,7,8,9]. Furthermore, eye changes may occur secondary to systemic diseases such as diabetes mellitus [10] or hypothyroidism [11]. Congenital eye malformations might be caused by a genetic disposition, as well as by exposure to toxins [12] or infections of the mother during pregnancy [13].…”
Section: Introductionmentioning
confidence: 99%
“… 14 Dogs with neoplasia frequently have hemostatic conditions including thrombocytopenia and hypercoaguability. 14 Direct infiltration of leukemic cells can manifest as retinal hemorrhage and may also be represented by gray‐white nodules, perivascular sheathing and rarely swelling of the optic nerve. 13 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…Neoplasia has been implicated in disrupting normal hemostatic mechanisms that can increase the risk for retinal hemorrhage according to one report 14 . Dogs with neoplasia frequently have hemostatic conditions including thrombocytopenia and hypercoaguability 14 . Direct infiltration of leukemic cells can manifest as retinal hemorrhage and may also be represented by gray‐white nodules, perivascular sheathing and rarely swelling of the optic nerve 13,15 …”
Section: Discussionmentioning
confidence: 99%
“…Subretinal haemorrhage can lead to retinal detachments [43]. An analysis of 83 dogs diagnosed with punctate retinal haemorrhage revealed a mean age of the patients of 10 years ± 3.8 [55]. A study performed on 42 hypertensive dogs revealed that 40 % of them had retinal haemorrhages [28].…”
Section: Hypertensive Chorioretinopathymentioning
confidence: 99%